2017
DOI: 10.1002/slct.201700824
|View full text |Cite
|
Sign up to set email alerts
|

Nanohydrotalcite Supported Ruthenium Nanoparticles: Highly Efficient Heterogeneous Catalyst for the Oxidative Valorization of Lignin Model Compounds

Abstract: The catalytic transformation of lignocellulosic biomass derived chemicals into value‐added chemicals under mild conditions remains a challenge in the fields of synthetic chemistry and catalysis. Herein, we describe a new heterogeneous catalyst system that efficiently works in the oxidative valorization of lignin model compounds. This new heterogeneous catalyst system comprised of nano‐sized hydrotalcite (n‐HT; Mg6Al2(CO3)(OH)16) supported ruthenium(0) nanoparticles (Ru/n‐HT) was prepared by ion‐exchange of [Ru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…As is known, the solvent is a very important metric for green and sustainable measures; 40 the solvents used in the existing methods are mainly organic solvents, such as alcohols, acetonitrile, DMSO, THF, DMF, 1,4-dioxane, acetone, xylene, EtOAc, etc . Although the conversion of vanillyl alcohol and the yield of vanillin were relatively high when acetonitrile, DMSO, THF, DMF, 1,4-dioxane, and acetone were used as solvents, among which acetonitrile was the best (the higher the polarity, the higher the conversion 41 ), they are classified as problematic and/or hazardous in CHEM21, 42 so it is not suitable as a solvent in Green Chemistry. By comparison, our study used alcohols and EtOAc as solvents, which were recommended solvents.…”
Section: Resultsmentioning
confidence: 99%
“…As is known, the solvent is a very important metric for green and sustainable measures; 40 the solvents used in the existing methods are mainly organic solvents, such as alcohols, acetonitrile, DMSO, THF, DMF, 1,4-dioxane, acetone, xylene, EtOAc, etc . Although the conversion of vanillyl alcohol and the yield of vanillin were relatively high when acetonitrile, DMSO, THF, DMF, 1,4-dioxane, and acetone were used as solvents, among which acetonitrile was the best (the higher the polarity, the higher the conversion 41 ), they are classified as problematic and/or hazardous in CHEM21, 42 so it is not suitable as a solvent in Green Chemistry. By comparison, our study used alcohols and EtOAc as solvents, which were recommended solvents.…”
Section: Resultsmentioning
confidence: 99%
“…Various other metal nanoparticles immobilized on a variety of carriers such as metal organic frameworks (MOFs), carbon, titania, and ceria have been also investigated. [59][60][61][62] Photocatalytic oxidations of vanillyl alcohol to vanillin over Ce and Zr oxide supported on biomass-templated titania were also reported by Muñoz-Batista and Luque et al 63 These smart materials showed excellent selectivity (99%) toward vanillin; however, the conversion of vanillyl alcohol was not great (maximum 52%). Similar photocatalytic conversion of vanillyl alcohol to vanillin under mild reaction conditions are reported by other groups.…”
Section: Introductionmentioning
confidence: 62%
“…Similarly, excellent selectivity could not be achieved using metal nanoparticles. [58][59][60][61][62] Although high selectivity could be achieved using photocatalysts, [63][64][65] poor conversion was a major issue in contrast to complete conversion achieved with the present catalyst. Hence, we can conclude that we have developed a significantly improved catalytic protocols as compared to the existing catalytic system for the aerobic oxidation of vanillyl alcohol to vanillin.…”
Section: Resultsmentioning
confidence: 99%
“…To investigate the effect of temperature on the rate of Ru/HTaL (50 mg, 1.12 wt% Ru) catalysed methanolysis of AB (100 mM in 5.0 mL of methanol), the catalytic reaction was performed at different temperatures (25,30,35,40, and 45°C). The initial rates at each temperature were determined from the linear portion of plots (volume of H 2 versus time) and used for the construction of Arrhenius and Eyring plots [41,42] from where activation parameters were determined.…”
Section: The Effect Of Temperature On the Rate Of Ru/htal Catalysed Mmentioning
confidence: 99%
“…Hydrotalcite-supported Pt [31], Pd [32][33][34], Ru [35], and Au [36] nanoparticles have been used as catalysts in hydrogenation, oxidation, and coupling reactions. The characterization of Ru/HTaL has been done by using various spectroscopic and visualization techniques including inductively coupled plasma optical emission spectroscopy (ICP-OES), powder X-ray diffraction (P-XRD), Fourier transform infrared spectroscopy (FTIR), 11 B NMR spectroscopy, X-ray photoelectron spectroscopy (XPS), scanning electron microscopy (SEM), bright field transmission electron microscopy (BFTEM), and high resolution transmission electron microscopy (HRTEM).…”
Section: Introductionmentioning
confidence: 99%